Male Engagement and Couples Communication in Reproductive, Maternal and Child Health in Nampula and Sofala Provinces of Mozambique - Findings from the Knowledge, Attitudes and Coverage Endline Qualitative Assessment - COWI; USAID; MISAU (2019)
This qualitative male engagement study by MCSP Mozambique evaluates the feasibility and acceptability of male engagement interventions that encouraged couples’ communication aimed at increasing antenatal care attendance, joint birth preparedness and complication readiness plans, institutional birth, and use of modern Family Planning. The study also explores how decisions between couples are made and what may influence their decisions about seeking RMNCH services.